가쓰오부시 훈연기 개선 및 벤조피렌 저감화 - 홍주희(Ju Hee Hong); 황상민(Sang Min Hwang); 이승주(Seung Ju Lee) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2017)
A Katsuobushi smoking machine was developed and evaluated to determine its benzo(a)pyrene reducing effect. The machine was equipped with two heaters for smoking and chamber heating. The smoke-generating system was equipped with a cadmium sulfide (CdS) smoke sensor, an on/off controller, and a rotating feeder with a smoke inlet. Raw bonito was steamed and then smoked under three smoke levels. After smoking at 45°C for 108 h, the benzo(a)pyrene concentrations were 5.87, 7.83, and 11.41 µg/kg at the low, middle, and high smoke levels, respectively. The benzo(a)pyrene concentrations after low-level smoking at 45, 65, and 85°C for 108 h were 5.87, 4.82, and 3.27 µg/kg, respectively. Accordingly, the optimal conditions for benzo(a)pyrene reduction were a lower smoke level and higher smoking temperature. These optimal smoking conditions can be implemented with the newly developed machine, but is not possible using a conventional Katsuobushi smoking machine.